Enriching experiences: Unpacking Kazakhstani EFL teachers' attitudes and readiness for intercultural approach - Kassymova, Gulnara; Tulepova, Saule; Bekturova, Madina (LPMPP Universitas Negeri Yogyakarta, 2025)
The present study aims to unpack the university English as a foreign language (EFL) teachers' practices and attitudes towards intercultural approach (ICA) and identify the prospective EFL teachers' level of preparedness to implement ICA. For this purpose, 36 EFL teachers and 45 master students doing a program on TEFL (Teaching English as a Foreign Language) were chosen to collect data through a survey and project analysis. The research findings indicate that despite recognising the intercultural paradigm in teaching EFL, embedded in all Kazakhstani regulations and the increasing tendency to use authentic textbooks; there is a lack of sound preparedness to implement ICA for both pre-service and in-service EFL teachers. Furthermore, the results suggest that two-thirds (66.6%) of master students could not identify all intercultural attributes in the coursebook. In-service teachers' agreement level on the importance of ICA is high; however, they lack practical skills for nuanced integration of ICA in EFL classrooms. This article can serve as a discussion platform to tackle challenges associated with ICA implementation in higher education not only in Kazakhstan but in the international context, as this issue is topical for many countries in the world where English is taught as a foreign language.